Strategi Kebijakan Transportasi dalam rangka Peningkatan Penggunaan Non-Motorized Transport Pelajar Sekolah Menengah di Jakarta Pusat - Afrian Argarima; Binsar Parasian Naipospos (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The potential for student travel movements reaches 3.8 million trips per day, equivalent to 20% of DKI Jakarta's total daily trips. This study aims to look at what factors influence the choice of mode decisions on school trips. The study involved a sample of 573 state high school students in Central Jakarta using stratified random sampling. The analytical method uses descriptive statistics and Multinomial Logit (MNL). The use of motorbikes accompanied by parents 47.29%, followed successively by walking 16.58%, private motorbikes 10.82%, public transportation 9.42%, online transportation 8.03%, accompanied by parents by car 3.14%, school buses 2.27%, using bicycles 2.09 % and private cars by 0.35%. Variables that influence the choice of student mode are gender, family size, amount of pocket money, school level, distance from home to school, travel time, motorized vehicle ownership and parents' occupation, with a Psedo R Squre Negelkerke value of 0.696, so the independent variables influence the dependent variable is 69.6% while the other 20.4% is influenced by variables outside the study. The school zoning policy (the distance from home to school is less than 2 km) convinced 59% of respondents who had previously chosen motorized transport to switch to walking mode. The policy of free bicycle facilities and Safe School Safe Routes (RASS) was able to convince 57.46% of respondents to switch modes of using bicycles on school trips